Upaya Pencapaian Zero Accident di PT. Sari Mas Permai - Novitasari, Nathania; Panjaitan, Togar W. S. (Jurnal Titra, 2015)
The effort to reach zero accident in PT. Sari Mas Permai is by applying SMK3 (Occupational Safety and Health Management System). The first step was by making a HIRARC document (Hazard Identification, Risk Assessment, and Risk Control) based on OHSAS 18001:2007 standard. HIRARC document is useful for every worker to know more about dangers and risks that exist in the working area, so every worker will be able to realize the importance of working safety and health and apply the risks control regularly. Hence the zero accident target will be accomplished. We used proactive technique in which the dangers are knowing before happened. The result of the analysis shows that risk control in PT. Sari Mas Permai has been successful to decrease high hazard by 32%, but there are 25 working activities in the 3rd plant with high and the medium risks, so risk control should be applied continuously.